The bronchoalveolar lavage fluid CD44 as a marker for pulmonary fibrosis in diffuse parenchymal lung diseases - Suchankova, Magda; Zsemlye, Eszter; Urban, Jan; Baráth, Peter; Kohútová, Lenka; Siváková, Barbara; Ganovska, Martina; Tibenska, Elena; Szaboova, Kinga; Tedlova, Eva; Juskanic, Dominik; Kluckova, Kristina; et al. (Frontiers in Immunology, 2025)
IntroductionDiffuse parenchymal lung diseases (DPLD) cover heterogeneous types of lung disorders. Among many pathological phenotypes, pulmonary fibrosis is the most devastating and represents a characteristic sign of idiopathic pulmonary fibrosis (IPF). Despite a poor prognosis brought by pulmonary fibrosis, there are no specific diagnostic biomarkers for the initial development of this fatal condition. The major hallmark of lung fibrosis is uncontrolled activation of lung fibroblasts to myofibroblasts associated with extracellular matrix deposition and the loss of both lung structure and function.MethodsHere, we used this peculiar feature in order to identify specific biomarkers of pulmonary fibrosis in bronchoalveolar lavage fluids (BALF). The primary MRC-5 human fibroblasts were activated with BALF collected from patients with clinically diagnosed lung fibrosis; the activated fibroblasts were then washed rigorously, and further incubated to allow secretion. Afterwards, the secretomes were analysed by mass spectrometry.ResultsIn this way, the CD44 protein was identified; consequently, BALF of all DPLD patients were positively tested for the presence of CD44 by ELISA. Finally, biochemical and biophysical characterizations revealed an exosomal origin of CD44. Receiver operating characteristics curve analysis confirmed CD44 in BALF as a specific and reliable biomarker of IPF and other types of DPLD accompanied with pulmonary fibrosis.